The value of econometrics to economists in business and government: a study of the state of the discipline. Issue 2 (2002) - Sowey, Eric R.
Abstract : This paper is the first ever in-depth study of the econometric practice of quantitative economists outside academia. It goes further, to examine empirically the often-heard proposition that academic and nonacademic economists nowadays seem to analyse the same applied quantitative problems in markedly separate ways. Nine indicators of separation between the approaches of 'town' and 'gown' economists are developed. The study rests on detailed interviews with 50 nonacademic economists drawn widely from a single area of professional activity: the Australian housing sector. These economists' use of econometric methods, and their views on the value of these methods, are documented and compared with the academic approach to applied econometric work, as reported in the scholarly literature. The evidence on the nine indicators supports the existence of a state of separation. The paper points to some undesirable consequences of separation and concludes with practical ideas on what should be done about it. There are lessons in the findings of this study for the future of other quantitative disciplines that are widely practised in government, business and industry.